Heritage crafts at Bou Saada Ksar: from the culture of industry to the cultural industry - LOUKRIZ, Larbi (The Algerian Historical Journal, 2026)
The traditional crafts and handicrafts of all kinds represent a material expression of the skills of artisans to meet the needs of individuals and groups of everyday tools and means., the Ksar of Bou Saada in the Saharan Atlas at the beginning of its foundation was based on agriculture and livestock breeding. After settling down, the population increased and many crafts emerged, which are still active today, representing a local heritage that preserves the experiences of generations. These crafts have developed and settled according to the needs of the people in a special urban environment, which represents an important aspect of the national identity and social and cultural history of Algeria.